2021
DOI: 10.3389/fcimb.2021.635335
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Metabolic Regulation Between Host and Pathogens: New Opportunities for the Development of Improved Therapeutic Strategies Against Mycobacterium tuberculosis Infection

Abstract: Mycobacterium tuberculosis (Mtb) causes chronic granulomatous lung disease in humans. Recently, novel strategies such as host-directed therapeutics and adjunctive therapies that enhance the effect of existing antibiotics have emerged to better control Mtb infection. Recent advances in understanding the metabolic interplay between host immune cells and pathogens have provided new insights into how their interactions ultimately influence disease outcomes and antibiotic-treatment efficacy. In this review, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 176 publications
0
13
0
1
Order By: Relevance
“…Succinate accumulation also leads to the generation mROS and NO and can stabilise hypoxia-inducible factor 1-alpha (HIF-1α). Activated HIF-1α further promotes the glycolytic pathway and lactate production and causes inflammation by positively regulating the glycolytic genes and IL-1β expression (52,59). In our study, Lactate dehydrogenase enzyme (Ldha) has been found to show enriched expression in the Ah infected group (AH group).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Succinate accumulation also leads to the generation mROS and NO and can stabilise hypoxia-inducible factor 1-alpha (HIF-1α). Activated HIF-1α further promotes the glycolytic pathway and lactate production and causes inflammation by positively regulating the glycolytic genes and IL-1β expression (52,59). In our study, Lactate dehydrogenase enzyme (Ldha) has been found to show enriched expression in the Ah infected group (AH group).…”
Section: Discussionmentioning
confidence: 61%
“…In our study, Lactate dehydrogenase enzyme (Ldha) has been found to show enriched expression in the Ah infected group (AH group). During this reprogramming, mitochondrial electron transport chain (ETC) is highly disturbed (52). In our study, we observed dysregulation of many proteins involved in ETC and OXPHOS.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…For instance, Ahr -/mice were unable to control M.tb H37Rv infection (212). Excellent recent reviews have further covered the potential intervention of metabolic pathways for HDT against TB (213)(214)(215)(216).…”
Section: Identifying Immune-metabolic Host Therapeutic Targetsmentioning
confidence: 99%